The Impact of Oxidative Stress and AKT Pathway on Cancer Cell Functions and Its Application to Natural Products - Jun-Ping Shiau; Ya-Ting Chuang; Jen-Yang Tang; Kun-Han Yang; Fang-Rong Chang; Ming-Feng Hou; Ching-Yu Yen; Hsueh-Wei Chang (MDPI AG, 2022)
Oxidative stress and AKT serine-threonine kinase (AKT) are responsible for regulating several cell functions of cancer cells. Several natural products modulate both oxidative stress and AKT for anticancer effects. However, the impact of natural product-modulating oxidative stress and AKT on cell functions lacks systemic understanding. Notably, the contribution of regulating cell functions by AKT downstream effectors is not yet well integrated. This review explores the role of oxidative stress and AKT pathway (AKT/AKT effectors) on ten cell functions, including apoptosis, autophagy, endoplasmic reticulum stress, mitochondrial morphogenesis, ferroptosis, necroptosis, DNA damage response, senescence, migration, and cell-cycle progression. The impact of oxidative stress and AKT are connected to these cell functions through cell function mediators. Moreover, the AKT effectors related to cell functions are integrated. Based on this rationale, natural products with the modulating abilities for oxidative stress and AKT pathway exhibit the potential to regulate these cell functions, but some were rarely reported, particularly for AKT effectors. This review sheds light on understanding the roles of oxidative stress and AKT pathway in regulating cell functions, providing future directions for natural products in cancer treatment.